2015
DOI: 10.1080/17441692.2015.1027247
|View full text |Cite
|
Sign up to set email alerts
|

Conducting an audit to improve the facilitation of emergency maternal and newborn referral in northern Ghana

Abstract: Ghana Health Service conducted an audit to strengthen the referral system for pregnant or recently pregnant women and newborns in northern Ghana. The audit took place in 16 facilities with two 3-month cycles of data collection in 2011. Midwife-led teams tracked 446 referred women until they received definitive treatment. Between the two audit cycles, teams identified and implemented interventions to address gaps in referral services. During this time period, we observed important increases in facilitating refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 8 publications
4
59
0
Order By: Relevance
“…Though often shrouded in taboo and stigma, research shows that sexual and reproductive health is fundamental to the economic development of nations, to people's health and survival, and to the wellbeing of humanity [42]. Compared to those in urban settings and of higher socio-economic status, women in rural settings, and those of lower socio-economic standing, tend to be more vulnerable to adverse physical, mental, obstetric and gynecological health outcomes [22,[43][44][45][46][47][48][49][50][51][52][53]. They often report poorer self-rated mental and physical health [43,52], have less access to necessary obstetric care [22,46,47,50], and have higher rates of trauma and mortality [23,24,46,[54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Though often shrouded in taboo and stigma, research shows that sexual and reproductive health is fundamental to the economic development of nations, to people's health and survival, and to the wellbeing of humanity [42]. Compared to those in urban settings and of higher socio-economic status, women in rural settings, and those of lower socio-economic standing, tend to be more vulnerable to adverse physical, mental, obstetric and gynecological health outcomes [22,[43][44][45][46][47][48][49][50][51][52][53]. They often report poorer self-rated mental and physical health [43,52], have less access to necessary obstetric care [22,46,47,50], and have higher rates of trauma and mortality [23,24,46,[54][55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…As a component of its initial response to gaps in essential services, GEHIP implemented a system of mortality audits to provide regional health managers with rapid feedback on preventable maternal and neonatal risks (Awoonor-Williams et al, 2015). In response to evidence that asphyxia was a prominent contributor to excess mortality, all frontline workers were trained in resuscitation management, referral services and essential emergency management.…”
Section: The Community-based Health Planning and Services Initiativementioning
confidence: 99%
“…In the current study, we found that 81.9% of referred patients arrived by means of public transport. This has been corroborated by others [2,3,6,16,29,30]. Even when ambulances are utilized, delay is often encountered as patients may need wait for ambulances to arrive from other locations or are asked to provide funds to fuel the vehicle [2, 4-6, 24, 29].…”
Section: Discussionmentioning
confidence: 79%
“…It is important to identify and categorize referral related barriers, whether considered Phase II or Phase III delay, in the provision of timely CEmOC in low resource countries and this topic remains vastly under-researched [2,6,26,27]. A strong referral system is characterized by communication and coordination along the referral pathway, with tailored referral protocols, patient support, protection against costs, and e cient transportation [2,6,16]. Having an effective and e cient referral system can reduce stillbirth, neonatal and maternal deaths [9,31].…”
Section: Discussionmentioning
confidence: 99%